(untitled) (Journal of the Entomological Research Society, 2019)
The European Red Wood ant Formica pratensis Retzius, 1793 (Hymenoptera: Formicidae) is a mound building ant species distributed in a number of countries in Europe and is listed in IUCN Red List of Threatened species with near-threatened status. The distributional range of the species in Turkey covers only the Thrace Region of the country. In the present study, we performed a three-stepped (inventory, monitoring and conservation) study to determine the current distribution of the species in the region and to propose a national red list status for the species. During the inventory and monitoring studies, a total of 340 localities were inspected in the region thoroughly for the presence of the colonies and a total of 89 colonies were recorded of which 20 died during the study period. The extent of occurrence (EOO) and area of occupancy (AOO) of the species were also measured. According to the evaluation of the distributional data, F. pratensis was assessed as Vulnerable (VU) in Thrace Region in Turkey following the criteria B1b (i, ii, iii, iv) due to the small AOO and EOO. The possible threats acting on the species were also discussed.